Post dielectric zinc oxide ceramic as well as preparation method and application thereof
By composting Li2O and Al2O3 doping on ZnO ceramics and using SPS sintering process, the problems of low dielectric constant, large dielectric loss and poor frequency stability of ZnO ceramics are solved, and ceramic materials with high dielectric constant and low dielectric loss are achieved, with good frequency stability and pun dielectric characteristics.
Patent Information
- Application Number
- CN202411828091.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-25
AI Technical Summary
The existing ZnO ceramic materials have low dielectric constant, large dielectric loss and poor frequency stability, and cannot have punctual dielectric characteristics.
The ZnO is combined with Li2O and Al2O3, and the dielectric properties of the ceramic are regulated by discharge plasma (SPS) sintering. The method includes dispersing zinc oxide and the modified filler in anhydrous ethanol, performing pre-sintering treatment, and subsequently sintering by SPS in a graphite mold, and applying external pressure to perform high temperature sintering.
The prepared zinc oxide ceramics have a dielectric characteristic, the dielectric constant is εr>104 at a frequency of 100Hz to 1MHz, the dielectric loss tanδ<0.1, and the frequency stability is good. It is suitable for filtering, energy storage, and timing control functions.
Smart Images

Figure CN119683991A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coarse dielectric zinc oxide ceramic and a preparation method and application thereof, belonging to the technical field of functional dielectric ceramics and preparation thereof. Background Art
[0002] As a basic component of the microelectronics industry, capacitors are widely used in power filtering, information coupling, etc. With the rapid development of the microelectronics industry, higher requirements are put forward for the intelligence, integration, and miniaturization of electronic components. The development of high-dielectric and low-loss functional dielectric ceramics is one of the effective ways to achieve the miniaturization of electronic components.
[0003] ABO3-based ceramics with perovskite structure and CaCu3Ti4O with perovskite-like structure 12 Based on ZnO, ceramics only have a colossal dielectric constant within a certain temperature and frequency range, and their application range is relatively narrow. As a typical varistor material, the conductivity characteristics of ZnO-based ceramics have been widely studied, but their polarization characteristics have been less studied. Since dense ZnO-based ceramics need to undergo long-term high-temperature calcination, a large number of Zn interstitial defects and oxygen vacancy defects are easily formed, which makes the dielectric loss of the ceramics large. Although the addition of sintering aids can reduce the sintering temperature of ZnO-based ceramics, inhibit the generation of defects and thus reduce dielectric loss, the dielectric constant of the ceramics will also decrease at this time, making it difficult to achieve both high dielectric constant and low dielectric loss at the same time. Therefore, it is necessary to develop ceramics that have both a colossal dielectric constant (ε r >10 4 ), low dielectric loss (tanδ<0.1) and good frequency stability of ZnO-based ceramics are of great significance. Summary of the invention
[0004] The present invention provides a colossal dielectric zinc oxide ceramic and a preparation method and application thereof to solve the problems that the existing ZnO ceramic material has low dielectric constant, large dielectric loss and poor frequency stability and cannot have colossal dielectric properties.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing a colossal dielectric zinc oxide ceramic, the method comprising the following steps:
[0007] (1) dispersing zinc oxide and modified filler in anhydrous ethanol, and ball milling to obtain a uniform mixed powder;
[0008] The modified filler includes Al2O3 and Li2O, and the molar ratio of the modified filler to zinc oxide is 0.1 to 0.2:1;
[0009] (2) pre-sintering the mixed powder to obtain pre-sintered powder;
[0010] (3) The pre-fired powder obtained in (2) is placed in a graphite mold, and sintered at high temperature by SPS sintering under external pressure to obtain zinc oxide ceramics.
[0011] It is further defined that the molar ratio of Al2O3 to Li2O in the modified filler is 1:1.
[0012] It is further defined that the mass of anhydrous ethanol in (1) is 5-5.2 times the total mass of zinc oxide and the modified filler.
[0013] It is further defined that in (1), the ball milling speed is 300 rad / min, the forward and reverse cycle period is 1 h, the ball milling time is 12 h, and the temperature is 20-30°C.
[0014] It is further defined that the pre-sintering process in (2) is: heating from 50°C to 800°C at a heating rate of 2°C / min and keeping the temperature for 1 hour.
[0015] Further, (3) the medium-high temperature sintering conditions are as follows: vacuum degree is 0.68 mbar, the temperature is increased from 50°C to 1100°C at a heating rate of 20-50°C / min, and the temperature is kept at this temperature for 30 min. After the temperature is kept at this temperature, the temperature is cooled to room temperature at a cooling rate of 5°C / min.
[0016] It is further defined that the externally applied pressure in (3) is 50 MPa.
[0017] The second object of the present invention is to provide a zinc oxide ceramic prepared by the above method.
[0018] It is further defined that the zinc oxide ceramic has a dielectric property, and at a frequency of 100 Hz to 1 MHz, the dielectric constant ε r >10 4 , dielectric loss tanδ<0.1.
[0019] The third object of the present invention is to provide an application of the above zinc oxide ceramic, specifically for the preparation of filtering, energy storage and timing control devices.
[0020] Beneficial effects:
[0021] The present invention adopts Li2O and Al2O3 to composite dope ZnO, and adopts discharge plasma (SPS) sintering method, and designs the dielectric properties of ZnO ceramics by composite doping and sintering process regulation to obtain colossal dielectric properties. On the one hand, the present invention adopts discharge plasma (SPS) sintering method to reduce sintering temperature and time, suppress the generation of its intrinsic defects, and reduce dielectric loss; on the other hand, Li2O and Al2O3 are used to composite dope ZnO, while suppressing intrinsic defects, and using the segregation of doped ions at grain boundaries to form grain boundary capacitance barriers, improve the dielectric constant of doped ceramics, so that the prepared zinc oxide-based ceramics have colossal dielectric properties, and good frequency stability, which can be used for filtering, energy storage and timing control and other functions, and can be applied to mobile electronic devices, automotive electronics, industrial equipment, communication equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD spectra of ceramics prepared in Examples 1 to 4 and a control group;
[0023] Figure 2 The dielectric constant of the ceramics prepared in Examples 1 to 4 and the control group varies with frequency;
[0024] Figure 3 The dielectric loss curves of the ceramics prepared in Examples 1 to 4 and the control group vary with frequency;
[0025] Figure 4 Impedance spectra of ceramics prepared in Examples 1 to 4 and a control group. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0030] Example 1
[0031] (1) Disperse zinc oxide in anhydrous ethanol, the amount of anhydrous ethanol used being 5 times the total mass of zinc oxide, and mix by planetary ball milling at room temperature for 12 hours, with a rotation speed of 300 rad / min and a forward and reverse cycle period of 1 hour to make the mixture uniform.
[0032] (2) Drying the mixed powder, specifically keeping it at 80° C. for 4 hours.
[0033] (3) The dried powder is passed through a furnace temperature control program, and the temperature is raised from room temperature to 800°C at a heating rate of 2°C / min, and sintered for 1 hour to obtain pre-burned powder.
[0034] (4) The pre-sintered powder is pre-mixed again using a mixer, the pre-mixing speed is 300 rad / min, the time is 12h, the forward and reverse cycle period is 1h, and the pre-mixing is dried at 60°C for 8h. The dried powder is poured into a graphite mold and pressurized at room temperature for 10min at a pressure of 10MPa; then the graphite mold is placed in a plasma furnace, the sintering environment is vacuum, the vacuum degree is 0.68mbar, the temperature is increased from 50°C to 1100°C at a heating rate of 50°C / min, and the temperature is kept at 50MPa during the sintering process. After the insulation is completed, the temperature is cooled to room temperature at a rate of 5°C / min to obtain zinc oxide ceramics.
[0035] Example 2
[0036] The difference between this embodiment and embodiment 1 is that: in (1), zinc oxide and modified filler are dispersed in anhydrous ethanol, the amount of anhydrous ethanol is 5 times the total mass of zinc oxide and modified filler, wherein the molar ratio of modified filler to zinc oxide is 0.2:1, and the modified filler is composed of Al2O3 and Li2O in a molar ratio of 1:1; the remaining process steps and parameter settings are the same as those in embodiment 1, and modified zinc oxide ceramics are obtained.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 2 is that the heating rate of the sintering process in (4) is 20°C / min, and the remaining process steps and parameter settings are the same as those in embodiment 2, thereby obtaining a modified zinc oxide ceramic.
[0039] Example 4
[0040] The difference between this embodiment and embodiment 2 is that: in (1), the molar ratio of the modified filler to zinc oxide is 0.1:1, and the remaining process steps and parameter settings are the same as those in embodiment 2 to obtain modified zinc oxide ceramics.
[0041] Example 5
[0042] The difference between this embodiment and embodiment 2 is that the heating rate of the sintering process in (4) is 100°C / min, and the remaining process steps and parameter settings are the same as those in embodiment 2. It is impossible to obtain highly densified ceramics, and it is impossible to carry out the next step of sample polishing and electrode preparation.
[0043] Example 6
[0044] The difference between this embodiment and embodiment 2 is that: during the sintering process in (4), the temperature is first increased from 50°C to 600°C at a heating rate of 100°C / min, and kept at this temperature for 0.5h, and then the temperature is increased from 600°C to 1100°C at a heating rate of 100°C / min, and kept at this temperature for 0.5h. After the end of the heat preservation, the temperature is cooled to room temperature at a cooling rate of 5°C / min. The remaining process steps and parameter settings are the same as those in embodiment 2. Compared with the sample obtained in embodiment 5, the density of the ceramic obtained is improved to a certain extent, but the next step of polishing and electrode preparation cannot be carried out.
[0045] Control group
[0046] The difference between this control group and Example 1 is as follows: (4) The pre-burned powder and the binder PVA aqueous solution are mixed in a mass ratio of 2:1, wherein the volume fraction of the PVA aqueous solution is 5vt%, and the molecular weight of PVA is 10000; the mixing method is: first use a mixer for premixing, the premixing speed is 40rad / min, and the time is 10min; then use a high-speed flying knife mixer for mixing, the barrel speed is 16rad / min, the flying knife speed is 1400rad / min, and the mixing time is 1.5h. After mixing, the mixed material is dried at 60°C for 8h. The dried powder is pressurized in air at room temperature for 10min, and the pressure is 15MPa to obtain a prefabricated block. The prefabricated block was placed in a high-temperature furnace, heated from 50°C to 1100°C at a heating rate of 10°C / min, kept warm for 1 hour, and then heated to 1250°C at a heating rate of 10°C / min, kept warm for 2.5 hours. After the insulation, the temperature was lowered to room temperature at a rate of 5°C / min to obtain zinc oxide ceramics.
[0047] Effect example
[0048] (1) X-ray diffraction analysis was used to characterize the crystal structure of the ceramics obtained in Examples 1 to 4 and the control group. The results are as follows: Figure 1 As shown by Figure 1It can be seen that, compared with PCPDF card #80-0075, the diffraction peaks of the ceramics obtained in Examples 1 to 4 and the control group are the same as the standard diffraction peaks of hexagonal wurtzite zinc oxide, which indicates that the ions of the modified filler can enter the zinc oxide lattice. In addition, in Examples 2 and 3, in addition to the standard peak position of wurtzite zinc oxide, the diffraction peaks of ZnAl2O4 appear at 2θ angles equal to 31.3° and 65.2°, indicating that Al 3+ At a higher content, the ions will precipitate at the grain boundaries in the form of a second phase. In Example 4, except for the standard peak position of wurtzite zinc oxide, no other diffraction peaks were observed, indicating that the modified filler ions completely entered the zinc oxide lattice and no second phase was precipitated.
[0049] (2) The dielectric frequency characteristics of the ceramics obtained in Examples 1 to 4 and the control group were characterized. The results are as follows: Figure 2 and Figure 3 As shown. Figure 2 and Figure 3 It can be seen that the dielectric constant of the zinc oxide ceramic in the control group is 1.8×10 8 , the dielectric loss is 48.5, and the dielectric constant and dielectric loss both decrease sharply with the increase of frequency at the frequency of 100Hz~1MHz. This is because the conductivity loss caused by the inherent defects of pure zinc oxide does not show the colossal dielectric properties. The impedance spectrum of the ceramics in the control group was further characterized, and the results are as follows Figure 4 As shown in the figure, the impedance spectrum of zinc oxide ceramics is consistent with the RC model through equivalent circuit model fitting, where R represents grain resistance, C represents capacitance, and the grain resistance is 1228Ω. This shows that since there are no grain boundaries with different conductivity, it is impossible to form a grain boundary capacitance barrier, and it also does not have colossal dielectric properties.
[0050] The dielectric constant of the ceramic of Example 1 is 8.5×10 7 , the dielectric loss is 34.14. However, the dielectric constant and dielectric loss still decrease seriously with the increase of frequency. Compared with the control group, Example 1 shows that the change of sintering method improves the dielectric properties of zinc oxide ceramics, which confirms the feasibility of the sintering process. The impedance spectrum of the ceramic of Example 1 is further characterized, and the results are as follows Figure 4 As shown, it can be seen from the equivalent circuit model RC that the grain resistance is 586Ω, which is lower than that of the control group, but neither of them forms a high-resistance grain boundary layer and does not exhibit colossal dielectric properties.
[0051] The dielectric constant of the ceramic of Example 2 at 100 Hz is 1.1×10 4The dielectric loss is only 0.1, and the dielectric properties do not drop significantly at frequencies of 100Hz to 1MHz. It also has a high dielectric constant of 7369 and a low dielectric loss of 0.09 at 1MHz, which shows that the addition of modified fillers improves the dielectric properties of ceramics and exhibits colossal dielectric properties. The impedance spectrum of the ceramic of Example 2 is further characterized, and the results are as follows: Figure 4 As shown in the figure, after fitting the equivalent circuit model, the impedance spectrum of the modified ceramic is g C(R gb C) has the best model fit. g is the grain resistance, with a resistance of 415Ω; R gb is the grain boundary resistance, with a resistance of 1.1×10 8 Compared with the control group and Example 1, the huge difference in conductivity between the semiconducting grains and the insulating grain boundaries of the modified ceramic induces the formation of grain boundary capacitance barriers, which is also the reason why it exhibits colossal dielectric properties.
[0052] The dielectric constant of the ceramic of Example 3 at 100 Hz is 2.5×10 4 , the dielectric loss is 0.3. Example 3 is opposite to Example 2. 6 The frequency stability at Hz is poor, but it shows colossal dielectric properties. This is because the reduction in the sintering heating rate increases the dielectric constant of the modified ceramic, but also reduces the suppression of intrinsic defects, increases the conductivity loss, and leads to an increase in its dielectric loss. The impedance spectrum of the ceramic of Example 3 is further characterized, and the results are as follows: Figure 4 As shown, the modified ceramic meets R g C(R gb C) Circuit model, its grain resistance R g The resistance value is 633Ω, and the grain boundary resistance R gb The resistance value is 1.3×10 6 Ω, with grains and grain boundary structures of different conductivity, can form grain boundary capacitance barriers, thus exhibiting colossal dielectric properties.
[0053] The dielectric constant of the ceramic of Example 4 at 100 Hz is 2.6×10 10 The dielectric loss is 862, and the frequency stability deteriorates sharply. The impedance spectrum of the ceramic of Example 4 is further characterized, and the results are as follows: Figure 4 As shown in the figure, the equivalent circuit model fitting result is an RC model, and the grain resistance R is only 117Ω. Since there is no barrier of insulating grain boundaries, the migration of carriers cannot be suppressed, which leads to an increase in conductivity loss, making it impossible for the modified ceramic to have colossal dielectric properties.
[0054] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a colossal dielectric zinc oxide ceramic, characterized in that: include: (1) dispersing zinc oxide and modified filler in anhydrous ethanol, and ball milling to obtain a uniform mixed powder; The modified filler includes Al2O3 and Li2O, and the molar ratio of the modified filler to zinc oxide is 0.1 to 0.2:1; (2) pre-sintering the mixed powder to obtain pre-sintered powder; (3) The pre-fired powder obtained in (2) is placed in a graphite mold, and sintered at high temperature by SPS sintering under external pressure to obtain zinc oxide ceramics.
2. The preparation method according to claim 1, characterized in that: The molar ratio of Al2O3 to Li2O in the modified filler is 1:
1.
3. The preparation method according to claim 1, characterized in that: (1) The mass of anhydrous ethanol is 5-5.2 times the total mass of zinc oxide and modified filler.
4. The preparation method according to claim 1, characterized in that: (1) The ball milling speed is 300 rad / min, the forward and reverse cycle period is 1 h, the ball milling time is 12 h, and the temperature is 20-30 °C.
5. The preparation method according to claim 1, characterized in that: (2) The pre-sintering process is as follows: heating from 50°C to 800°C at a heating rate of 2°C / min and keeping the temperature for 1h.
6. The preparation method according to claim 1, characterized in that: (3) Medium-high temperature sintering conditions are as follows: vacuum degree is 0.68 mbar, heating rate is 20-50°C / min, heating from 50°C to 1100°C, and heat preservation is performed for 30 min. After heat preservation, cooling is performed at a rate of 5°C / min to room temperature.
7. The preparation method according to claim 1, characterized in that: (3) The internal and external pressure is 50MPa.
8. A zinc oxide ceramic prepared by the method according to any one of claims 1 to 7.
9. The zinc oxide ceramic according to claim 8, characterized in that: The zinc oxide ceramic has a large dielectric property. At a frequency of 100Hz to 1MHz, the dielectric constant ε r >10 4 , dielectric loss tanδ<0.
1.
10. An application of the zinc oxide ceramic according to claim 8, characterized in that: Used for the preparation of filtering, energy storage and timing control devices.